Traditional midwives
1 online resource (xviii, 467 pages)
Keywords: "Traditional midwives, shedding light on their practices, roles, and the immense cultural value they hold within their respective communities wherever they are still allowed to practice. This book not only champions the significance of traditional midwifery but also critiques the (often misguided) global and national initiatives that seek to move all childbirths into biomedical facilities, which, as the chapters in this book clearly show, are frequently under-equipped and under-staffed and provide substandard care that can often be obstetrically violent and abusive. The push to move all births into such facilities disregards the quality of care that traditional midwives provide and undermines the trust and rapport they have built within their respective communities. This global push is particularly detrimental to rural women because biomedical facilities are often located far away from such communities, thereby making access to maternity care difficult, if not impossible, especially for rural women, and because almost no biomedical practitioners are willing to live and practice in such remote areas, thereby leaving thousands of (especially rural) women without any maternity care provision. Other critical points that this book addresses are the failures of the governmental efforts to train traditional midwives in higher-level skills. As the chapters in this book also clearly demonstrate, the essence of traditional midwifery lies in experiential learning, where skills are passed down through observation, practice, and mentoring. By bringing to light the multiple challenges that are currently being faced by traditional midwives and the shortcomings of biomedical facilities, this book serves as a crucial reminder of the need for culturally safe and sensitive community-based maternity care that traditional midwives are fully able to provide. It is an essential read for policymakers, healthcare professionals, students, and for anyone who is interested in traditional midwives and their practices"-- Provided by publisher.